Angiogenic Potential of Human Neonatal Foreskin Stromal Cells in the Chick Embryo Chorioallantoic Membrane Model - Radhakrishnan Vishnubalaji; Muhammad Atteya; May Al-Nbaheen; Richard O. C. Oreffo; Abdullah Aldahmash; Nehad M. Alajez (Stem Cells International)
Several studies have demonstrated the multipotentiality of human neonatal foreskin stromal cells (hNSSCs) as being able to differentiate into adipocytes and osteoblasts and potentially other cell types. Recently, we demonstrated that hNSSCs play a role during in vitro angiogenesis and appear to possess a capacity to differentiate into endothelial-like cells; however, their angiogenic potential within an ex vivo environment remains unclear. Current study shows hNSSCs to display significant migration potential in the undifferentiated state and high responsiveness in the in vitro wound healing scratch assay. When hNSSCs were seeded onto the top of the CAM, human von Willebrand factor (hVWF), CD31, smooth muscle actin (SMA), and factor XIIIa positive cells were observed in the chick endothelium. CAMs transplanted with endothelial-differentiated hNSSCs displayed a higher number of blood vessels containing hNSSCs compared to CAMs transplanted with undifferentiated hNSSCs. Interestingly, undifferentiated hNSSCs showed a propensity to differentiate towards ectoderm with indication of epidermal formation with cells positive for CD1a, CK5/6, CK19, FXIIIa, and S-100 cells, which warrant further investigation. Our findings imply a potential angiogenic role for hNSSCs ex vivo in the differentiated and undifferentiated state, with potential contribution to blood vessel formation and potential application in tissue regeneration and vascularization.